La falta de criterios dentro del ordenamiento jurídico peruano respecto del concepto de «originalidad» aplicado a la protección de los derechos de autor sobre imágenes fotográficas - Chávez Gutierrez, Wendy Elizabeth (2014)
In our legal system, Copyright Law confers protection to authentic photographies and due to this feature, they are considered photographic works. Nevertheless, authorities have not given enough information of what a photography requires to be considered authentic. On account of this, the shortcomings of our related rules are evaluated to determine which foreign legislation gives a better referent, and to analyze the different views given to the authenticity concept by doctrine and case law. All of this with the purpose of determining specific criteria to qualify a photography as authentic and protected by Copyright Law, and proposing changes in our current legislationon the matter.